김일성사회주의청년동맹의 사회통합적 기능에 관한 연구 - 차승주; Seung Joo Cha (글로벌정치연구, 2011)
이 논문은 북한의 ``김일성사회주의청년동맹``이 사회통합기제로서 가지는 역할과 특성을 분석한 것이다. 북한 최대의 근로단체이자 사회단체인 ``김일성사회주의청년동맹``은 1946년 1월에 결성되었다. 북한은 청년들의 대부분을 포함하고 있는 조직인 청년동맹을 당, 군과 함께 체제유지를 위한 3대 보루의 하나로 인식하고 있다. 청년동맹이 수행하고 있는 사회통합적 기능은 다음과 같다. 첫째, 정치적 기능으로 청년동맹에게 요구된 가장 우선적이고도 중요한 과제는 김일성에 대한 변함없는 충성과 김정일에 대한 대를 이은 충성이다. 이러한 요구는 자연스럽게 군사적인 측면의 역할 기대로 이어지게 된다. 둘째, 경제적 기능으로 청년동맹에게는 정치·군사적 기능 이외에 경제적 기능 역시 강조되고 있다. 현재 북한에서 청년들은 군대와 함께 노력동원의 핵심이고, 청년동맹에게 요구되고 있는 경제지원활동은 그 범위와 중요성이 더욱 커지고 있다. 셋째, 사상·문화적 기능으로 일반적으로 청년동맹에 대해 언급할 때 가장 먼저 제기되는 것은 바로 사상교양단체로서의 역할이다. 청년동맹은 생활총화나 학습 등을 통해서 동맹원들에게 당과 수령에 대한 충실성교양, 혁명교양, 계급교양, 사회주의 애국주의 교양, 공산주의 교양 등을 실시하고 있다. The main objective of this study is to analyze the roles and features of ``Kim Il Sung Socialist Youth League`` as a mechanism for social integration. It was found on January, 1946. The North Korean government recognizes that it is a bastion of controlling and survival of North Korea. Contributions that the ``Kim Il Sung Socialist Youth League`` make towards social integration of North Korean society may be summarized as follows: First, the League brainwashes its youth members to accept the statuses and roles imposed upon them by the regime as the major players in the future in the form of ``reserve forces for the communist party,`` ``successors of the revolution,`` and ``faithful servants`` to the Kims as ``guardsmen tirelessly loyal to the party`` and ``bombs that boldly guard the General,`` always appreciating the love and generosity of the Supreme Leader and the Honorable General. Second, the members of the League almost automatically accept the practice of social-economic mobilization as something routine and natural. They would plant trees, crops, and flowers, collect rabbit leather, idle and waste matters, or even composts. Third, The central goal of the ``Kim Il Sung Socialist Youth League`` is to inculcate in the minds of the younger generation from their relatively early childhood Kim`s juche ideology of North Korea and societal values intended to uphold their unique socialist orientations.